A COMPARATIVE STUDY ON THE EFFECT OF COOPERATIVE LEARNING MODELS GI, TGT, AND STAD ON ELEMENTARY STUDENTS MATHEMATICAL DISPOSITION - Mela Minkhatul Maula; Maulana Maulana; Isrokatun Isrokatun (Jurnal Cakrawala Pendas, 2025)
The role of learning models is crucial in achieving educational objectives, particularly in mathematics, which is often perceived as a challenging subject by students. This study examines the comparative effectiveness of learning models in enhancing mathematical disposition while controlling for students’ prior knowledge and gender variables. A quasi-experimental pretest-posttest control group design was employed, with the population consisting of elementary schools across Cirebon Regency and a sample of 90 students from three schools. Data collection techniques included a mathematical disposition scale and documentation of students’ academic scores.  The results indicate that the cooperative learning models GI (Group Investigation), TGT (Teams Games Tournament), and STAD (Student Teams Achievement Division) have varying impacts on students’ mathematical disposition. The GI model showed the most significant effect, with an average increase of 7.8%. Students’ prior knowledge also played a role, as those with higher initial abilities tended to exhibit better mathematical dispositions. However, no significant differences were found in mathematical disposition between male and female students. This suggests that the GI model can be an effective choice for teachers to foster a positive attitude toward mathematics, especially among students with higher prior knowledge.